Risk perception influences athletic pacing stategy - Micklewright, D.; Parry, D.; Robinson, T.; Deacon, G.; Refre, A.; Gibson, A. St. C.; Mathews, W. (Medicine & Science in Sports & Exercise, 2015)
Purpose: The objective of this study is to examine risk taking and risk perception associations with perceived exertion, pacing, and performance in athletes.